Intra- and intermolecular hydrogen bonding and conformation in 1-acyl thioureas: An experimental and theoretical approach on 1-(2-chlorobenzoyl)thiourea - Saeed, Aamer (2015)
The vibrational analysis (FT-IR and FT-Raman) for the new 1-(2-chlorobenzoyl)thiourea species suggests that strong intramolecular interactions affect the conformational properties. The X-ray structure determination corroborates that an intramolecular N-H⋯OC hydrogen bond occurs between the carbonyl (-CO) and thioamide (-NH2) groups. Moreover, periodic system electron density and topological analysis have been applied to characterize the intermolecular interactions in the crystal. Extended N-H⋯SC hydrogen-bonding networks between both the thioamide (N-H) and carbamide (NH2) groups and the thiocarbonyl bond (CS) determine the crystal packing. The Natural Bond Orbital (NBO) population analysis demonstrates that strong hyperconjugative remote interactions are responsible for both, intra and intermolecular interactions. The Atom in Molecule (AIM) results also show that the N-H⋯Cl intramolecular hydrogen bond between the 2-Cl-phenyl ring and the amide group characterized in the free molecule changes to an N⋯Cl interaction as a consequence of crystal packing.